A Rare Case of Subacute Sclerosing Panencephalitis Presenting As Generalized Seizure - Simkhada, Nabin (Cureus, 2021)
Subacute sclerosing panencephalitis (SSPE) is a late complication of childhood measles. It is characterized by a progressive decline in cognitive and motor functions, seizures, and eventually death. Although a combination of intrathecal interferon alpha (IFN-α) and daily oral isoprinosine has been reported to have a good outcome, there is no cure for this condition.  We present a case of a 16-year-old male with SSPE who presented with progressive weakness, frequent loss of postural control, multiple episodes of generalized tonic-clonic seizures, and urinary incontinence. On exploration of his history, he had measles at the age of two months. Investigation showed increased serum measles antibody titer, high amplitude spikes in electroencephalogram (EEG), and high fluid-attenuated inversion recovery (FLAIR) signals on MRI of the brain consistent with probable SSPE. He was managed symptomatically until his condition got worse and he eventually passed away.